Malakah Al-Fikr Menurut Pemikiran Ibn Khaldun: Kajian Terhadap Amalan Kbat Guru Pendidikan Islam Dalam Pengajaran Di Sekolah Rendah - Zulkufli, Mohd Azolman (2021)
Studies have shown successful implementation of Higher Order Thinking Skills (HOTS) in Islamic Education is dependent on Islamic Education Teachers’ (IETs) readiness, knowledge and skills to plan and prepare HOTS-based lessons. Thus, this study aims to examine the integration of HOTS in IET’s teaching practices in primary schools and to explore Ibn Khaldun's thoughts embedded in the lessons.